REKONSTRUKSI PEMIKIRAN ISLAM TERHADAP BATASAN DAN KEBEBASAN BEREKSPRESI SENI DI ERA DIGITAL - Lelah Nurjamilah; Suci Dwi Kurniasih; Helmawati Helmawati; Iyad Suryadi (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
The dynamics of modern art in the digital era open up broad spaces for freedom of expression, including among students in Islamic higher education. However, artistic expression must remain in harmony with Islamic values and the boundaries of Sharia. This study aims to analyze how students at KH. Cipasung Islamic University (UNIK Cipasung) perceive art from an Islamic perspective, identify the forms of their artistic expression, and examine the reconstruction of Islamic thought that emerges. The research uses a descriptive qualitative approach with data collection techniques including interviews, field observations, and document studies involving ten students. The findings indicate that students understand art as an expression of beauty grounded in Islamic values, as well as a medium for education and da'wah. Their freedom of expression is selective and responsible, not adopting the concept of absolute freedom typical of Western liberalism. There is a reconstruction of Islamic thought that integrates normative religious values with modern artistic practices, resulting in an adaptive, moderate, and contextual understanding. The study concludes that students are able to harmonize artistic creativity with Islamic ethical principles, ensuring that freedom of expression remains within the framework of Islamic values.  ABSTRAK Dinamika seni modern di era digital membuka ruang kebebasan berekspresi yang luas, termasuk di kalangan mahasiswa perguruan tinggi Islam. Namun, ekspresi seni tetap harus selaras dengan nilai-nilai Islam dan batasan syariat. Penelitian ini bertujuan menganalisis bagaimana mahasiswa Universitas Islam KH. Cipasung (UNIK Cipasung) memaknai seni dalam perspektif Islam, mengidentifikasi bentuk-bentuk kebebasan berekspresi mereka, serta menelaah rekonstruksi pemikiran Islam yang berkembang. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data wawancara, observasi lapangan, dan studi dokumen terhadap sepuluh mahasiswa. Hasil penelitian menunjukkan bahwa mahasiswa memahami seni sebagai ekspresi keindahan yang tetap berpegang pada nilai-nilai Islam, sekaligus sebagai media edukasi dan dakwah. Kebebasan berekspresi mereka bersifat selektif dan bertanggung jawab, tidak mengadopsi konsep kebebasan absolut ala liberal Barat. Terjadi rekonstruksi pemikiran Islam yang mengintegrasikan nilai normatif agama dengan praktik seni modern, menghasilkan pemahaman yang adaptif, moderat, dan kontekstual. Simpulan penelitian ini adalah mahasiswa mampu menyelaraskan kreativitas seni dengan prinsip etika Islam, sehingga kebebasan berekspresi tetap berjalan dalam koridor nilai-nilai keislaman.